Exploiting ozonolysis-microbe synergy for biomass processing: Application in lignocellulosic biomass pretreatment. (October 2017) - Mulakhudair, Ali R.; Hanotu, James; Zimmerman, William
Abstract: Pretreating lignocellulosic biomass is an energy and time consuming process. This study presents an alternative pretreatment technique, which explores a synergistic approach between ozonolysis and cellulolytic microorganism-Pseudomonas putida at room temperature. Ozone is a strong oxidative agent that reacts with lignin by attacking the carbon-carbon double bonds, while P. putida preferentially hydrolyses the exposed cellulolytic parts of the biomass to simple sugars. The results from SEM and FTIR show a significant reduction in lignin and cellulose contents, leading to relatively high sugar recovery. The glucose concentration increases coincidentally with the ozonation duration and After 24 h however, the concentration reached 1.1 mg/ml, a 323% increase compared with results after 2 h. Increasing the ozonation time to 24 h reduced the biological pretreatment time by 50% but crucially, increases microbial biomass. This approach has potentially high ramifications particularly for industries exploiting lignocellulosic biomass as a feedstock for bioethanol production. Highlights: Ozone is a strong oxidative agent that reacts with lignin by attacking the carbon-carbon double bonds. P. putida releases cellulolytic enzymes, which preferentially hydrolyses the exposed cellulolytic parts of the biomass to glucose. The ozone-microbe pretreatment technique brought about both physical and chemical alterations to the biomass structure. The ozone-microbe synergy is more effective and efficient than either solo option for pretreatment of lignocellulosic biomass. Ozonolysis contributed more in this synergy than the biological pretreatment.